Pengaruh Budaya Organisasi terhadap Kinerja Guru melalui Kepuasan Kerja sebagai Variabel Mediasi pada SMK SMTI Banda Aceh - Chumaira Sofyan; Hj. Nadiya; Sulfitra Sulfitra (Politeknik Kampar, 2025)
This study seeks to investigate and analyze how organizational culture affects teacher performance, with job satisfaction acting as a mediating variable at SMK SMTI Banda Aceh. The research involved a sample of 55 teachers from the institution who willingly participated as respondents. Data was gathered using a questionnaire designed for this purpose.